Sibutramine: A banned innocent antiobesity drug (Journal of Pharmaceutical Negative Results, 2016)
Obesity is a major public health problem. In spite of manydietaries and lifestyle suggestions, more than 80% of affectedcases cannot achieve weight loss.[1] Sibutramine is a combinednorepinephrine and serotonin reuptake inhibitor attributeto the enhancement of satiety and decrease in caloric intakeinstead of anorectic action. Sibutramine was approved in1998 and has been widely evaluated in several trials, whichtake place between 16 and 52 weeks